The quest for infrastructure development from a “market creation” perspective: China's “Belt and Road”, Japan's “Quality Infrastructure” and the EU's “Connecting Europe and Asia” - Werner Pascha (International Economics and Economic Policy, 2020)
The paper deals with the interplay of major international infrastructure initiatives, in particular China's Belt and Road Initiative, Japan's Partnership for Quality Infrastructure and the EU strategy on “Connecting Europe and Asia”. Their co-evolution is interpreted as the creation and further development of a new market, whose characteristics like its complexity, its properties as an international public good and its oligopolistic supply structure create interesting insights. The paper finds that initiatives have adjusted to each other, in line with expectations from a market perspective. While China's initiative at first followed a “low-price” strategy, Japan reacted with a “quality infrastructure” approach, also winning support from multilateral fora like G7 and G20. With the Second Belt and Road Forum, China has signaled to move closer to this line as well, and the EU is pursuing a similar approach as Japan, signing a partnership agreement with it. Interpreting this interaction as an oligopolistic structure, a chaotic competitive process has so far been avoided. The contest is actually evolving towards superior solutions, raising the quality of institutional infrastructure initiatives and, hopefully, of specific projects as well.
Keywords: F53; F55; H87; L91; O19; P45; 330; Infrastructure; Connectivity; Belt and road initiative; China; Japan; European union